Office Ergonomics Program To Reduce Musculoskeletal Disorder Among Computer Users Of Malaysia’s Oil And Gas Industry - Choong, Chwee Ching (Open University Malaysia, 2021)
Background: In the past two decades, office work is rapidly changing with development of new computer technology that increase the efficiency of our work. Office employees usually spend 40 hours or more per week at their office computer workstation. This has placed office environment as a significant roles into employees’ daily life. In recent years, there have been increasing attention on Office Ergonomics. Office Ergonomics is the science of establishing the best fit between a worker and the tasks they carry out and working environment. In simple words, office ergonomics is where the office employees can comfortably and effectively carry out their job with the correct furniture, equipment and working condition. The long hour of working with computers or laptops have been associated with an increase in work related musculoskeletal disorder (WMSDs). Methodology: The survey questionnaire was designed and distributed via GoogleForm. 161 office computer users in selected Malaysia’s Oil and Gas Industry has responded to the questionnaire. The survey data was validated, received for data entry-encoding and analyzed for quantitative descriptive analysis. Result: The survey indicated that 94.4% of the respondents’ have established office ergonomics program for the computers users by the companies. Approximately 83.85% of the respondents had encountered MSDs at different frequency. The survey concluded that neck (52.8%) and shoulder (48.7%), lower back (37.9%) are the most commonly have MSDs for office computer users. 111 respondents (88%) seen an improvement both in managing the musculoskeletal disorder and improved work productivity. Conclusion: Office ergonomics program is key to managing and improving musculoskeletal disorders among office computer users.